Childhood adversity and social functioning in psychosis: Exploring clinical and cognitive mediators. (30th April 2016) - Palmier-Claus, Jasper; Berry, Katherine; Darrell-Berry, Hannah; Emsley, Richard; Parker, Sophie; Drake, Richard; Bucci, Sandra
Abstract: Childhood adversity may increase risk of impaired social functioning across the continuum of psychosis. However, the pathways by which adversity dictates functional outcome remain underexplored. This study investigated the association between childhood adversity and social functioning, and the clinical and cognitive mediators of this relationship. Fifty-four clinical (20 chronic, 20 first episode, 14 at ultra-high risk) and 120 non-clinical participants completed standardised questionnaires, semi-structured interviews and tests of theory of mind ability. The authors used multiple group structural equation modelling to fit mediation models allowing for differential relationships between the clinical and non-clinical samples. When examining each pathway separately, depression, paranoia and anxious attachment mediated the effect of childhood adversity on social functioning. In a combined model, depression was the only significant mediating variable with greater adversity predicting lower mood across groups. Childhood adversity did not significantly predict theory of mind ability in any of the models. This is the first study to indicate that childhood adversity acts on social functioning by increasing levels of depression, suggesting a common mechanism across the spectrum of psychosis. Clinical interventions should target low mood in order to improve social functioning at all stages of psychotic disorder. Highlights: Childhood adversity acted on social functioning by increasing levels of depression. Treating depression in people with a trauma history may enhance social functioning. Childhood adversity was not found to be associated with theory of mind ability.